2017
DOI: 10.1002/jbm.b.33834
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory coatings of hernia repair meshes: A pilot study

Abstract: The current prevalence of postoperative chronic pain from hernioplasty procedures employing polymer mesh is close to 30%. Most of the researchers agree that oxidative stress, resulting from the release of oxidants and enzymes during acute inflammatory response, is a key factor in the development of posthernioplasty complications. This results in both the decrease of the biomechanical properties and stiffening of the polymer fibers of the mesh, leading to chronic pain. Moreover, enhanced activity of inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…For all animals individually, the difference was statistically significant too. Additionally, little to no evidence of foreign body giant cells was found in the vicinity of either of the implants, similarly to the pilot study [20]. The numerical data are presented in Table 2.…”
Section: Histological Evaluationsupporting
confidence: 62%
See 4 more Smart Citations
“…For all animals individually, the difference was statistically significant too. Additionally, little to no evidence of foreign body giant cells was found in the vicinity of either of the implants, similarly to the pilot study [20]. The numerical data are presented in Table 2.…”
Section: Histological Evaluationsupporting
confidence: 62%
“…In a pilot one-rabbit study, we showed that vitamin E-coated meshes exhibited reduced foreign body response and improved wound healing [20]. Furthermore, in vitro release of vitamin E from the coated mesh was desirably slow, with 70% of the coating remaining after 10 days of exposure to albumin solution, suggesting sustained release and long-term protection [20]. However, pilot nature of the study yielded limited statistical data.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations